2003
DOI: 10.1038/sj.ejcn.1601651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of predominant methanogenic flora on the outcome of lactose breath test in irritable bowel syndrome patients

Abstract: Patients with predominant fasting methane production excrete less H(2) than LMP, after an oral load of lactose. The lower prevalence of severe lactose intolerance in PMP, as well as lower incidence of symptoms during the test, is, indeed, related to lower and slower H(2) excretion. The assumption that H(2) excretion is an effective means of quantifying the amount of malabsorbed carbohydrates is questionable in PMP. Methane-producing patients likely have a higher 'false negative' rate as compared to LMP after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Conversely, the increase in H 2 concentrations in expired air was associated with the reduction or suppression of CH 4 excretion. Similar results were observed by Vernia et al [9], in an Italian population. As expected, subjects with predominant CH 4 -producing flora excrete lower amounts of H 2 as compared to low CH 4 producers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, the increase in H 2 concentrations in expired air was associated with the reduction or suppression of CH 4 excretion. Similar results were observed by Vernia et al [9], in an Italian population. As expected, subjects with predominant CH 4 -producing flora excrete lower amounts of H 2 as compared to low CH 4 producers.…”
Section: Discussionsupporting
confidence: 90%
“…Methane-producing patients likely have a higher ''falsenegative'' rate as compared to LMP after an oral load of lactose. Nonetheless, as symptoms are related to the amount of gas produced in the colon, HBT identifies patients with ''lactose intolerance,'' irrespective of the presence of lactose malabsorption, and helps in predicting the effect of a lactose-restricted diet [9]. Kajs et al [10] investigated the possibility that a variant of the normal colonic flora, a high concentration of methanogens, influences the host's response to ingestion of non-absorbable, fermentable materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the peak values of hydrogen excretion in PMPs also showed lower values than in the LMP group, both in controls as well as in IBS patients. Similar findings have been reported by Vernia et al [7].…”
Section: Discussionsupporting
confidence: 89%
“…A field study was performed to determine the prevalence of lactose malabsorption in Myanmar children and to evaluate the possibility of using breath methane excretion to indicate lactose malabsorption in a field situation [6]. The relationship between hydrogen and methane production is a possible confounding factor in the interpretation of the results of HBTs, but it is usually disregarded and, in most instances, only H 2 excretion is measured [7]. It has been suggested that in methanogenic individuals, breath CH 4 measurement might enhance the accuracy of H 2 breath testing in detecting carbohydrate malabsorption [8].…”
Section: Introductionmentioning
confidence: 99%
“…IBS might be a key confounding factor because it is a common entity and its clinical expression, particularly diarrhea-predominant IBS, which includes loose stools, audible bowel sounds, abdominal pain and meteorism resembles the symptoms produced by lactose malabsorption [39,40]. Furthermore, IBS patients might be particularly hypersensitive to lactose compared with healthy individuals [41].…”
Section: Discussionmentioning
confidence: 99%